Some Importance Properties of Bamboo-Wood Strand Board - Ihak Sumardi; Yoyo Suhaya; Tito T. Putra (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
Bamboo has gained increasing attention as an alternative raw material for use in the manufacture of composite boards. Three layered boards were made from bamboo strand and wood particle to evaluate the effects of resin content and layer structure on the properties of bamboo-wood strand board. Bamboo strand was used as face/back layers, and wood particle was used as core layer. The boards were fabricated using urea formaldehyde resin with three dosage levels ranging from 3 to 9 percent for bamboo strand and 6 percent resin content for wood particle. The mechanical properties and dimensional stability of bamboo-wood strand board were evaluated, and the results were summarized as follows. The bending properties, internal bond (IB) strength and dimensional stability of the board increased with increasing of resin content. Using bamboo strand as face/back layered, slightly increase bending properties of bamboo-wood strand board. However, the modulus constant and IB strengths after boiling test could not be observed. It indicates that urea formaldehyde was not suitable for bamboo-wood strand board.